Description of a second species of Gymnoxenisthmus from the Red Sea (Teleostei: Gobioidei: Xenisthmidae) - Gill, Anthony C.; Bogorodsky, Sergey V.; Mal, Ahmad O. (Zootaxa, 2019)
Gymnoxenisthmus flavicinctus n. sp. is described from the 20.2 mm SL holotype collected from Sharm Obhur, Jeddah, Saudi Arabia, central Red Sea. It differs from the holotype and only known specimen of its congener G. tigrellus in having entirely unbranched pectoral-fin rays (versus only upper two rays and lowermost ray unbranched), 17 (versus 15) pectoral-fin rays and 13 (versus 12) segmented anal-fin rays. It also differs in live and preserved coloration. The new species brings the total number of xenisthmids known from the Red Sea to five.